Privacy and Anonymity - Dayakar Siramgari (International Journal of Intelligent Systems and Applications in Engineering, 2019)
In the digital era, privacy and anonymity are becoming increasingly crucial because of widespread monitoring and data collection by corporations and governments. This study examines the ethical, legal, and technological aspects of privacy and anonymity, particularly in relation to surveillance capitalism, commodification of personal data, and individuals' expectations of privacy. It discusses the distinction between privacy and anonymity, highlighting the need for privacy-preserving measures such as encryption, differential privacy, and anonymization techniques. Additionally, this study explores the challenges associated with privacy, such as data re-identification risks, and reviews technological solutions, including end-to-end encryption, federated learning, and blockchain. The study also covers regulatory frameworks such as the GDPR, evaluates privacy-preserving technologies, and analyzes the ethical balance between privacy rights and security needs. Real-world applications and case studies illustrate the implementation of privacy mechanisms in various industries, emphasizing the importance of privacy and anonymity protection to uphold individual rights in data-driven landscapes.